Differences in gut microbiota in rat models of cardiovascular disease - Thiba, Anza (My University, 2018)
Approximately 25% of the world’s adult population has hypertension. Hypertension is a major risk factor for cardiovascular disease, stroke, and heart and kidney failure; however, the cause remains unknown. Gut microbiota have been shown to have a causal role in the development of hypertension. In animal studies, it has been shown that eradication of certain gut microbiota leads to decreased blood pressure and that gut dysbiosis may cause an increase in blood pressure. Furthermore, there is a difference in microbial flora composition in hypertensive and normotensive rats. The aim of this study was to compare the diversity and abundance of gut microbiota in animal models of hypertension. Stomach, intestinal and faecal samples were harvested from spontaneously hypertensive rats (SHR), Dahl salt sensitive rats (SSR) and normotensive Dahl rats. The samples were cultured in microaerophilic conditions (5% O2–10% CO2–85% N2) and identified by matrix assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF). Genomic DNA isolation, 16S rRNA gene sequencing, and analysis of microbial composition were performed on the samples. There was decrease in microbial species diversity, richness, and abundance in the hypertensive rat models. In addition, there a was an increase in Firmicutes and Bacteroidetes ratio in the hypertensive rat models. The observed results demonstrate that a dysbiotic gut microbiota is associated with hypertension. Previous studies have shown that bacteria from Bacteroidetes and Firmicutes play a crucial role in development of hypertension and are needed for the maintenance of physiological homeostasis.
A dissertation submitted to the faculty of Health Science, University of the Witwatersrand, for the degree of Master of Science in Medicine, November 2018